2016
DOI: 10.1002/lary.26419
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of endoscopic and videofluoroscopic evaluations of swallowing for oropharyngeal dysphagia

Abstract: 2a Laryngoscope, 127:2002-2010, 2017.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
100
1
6

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 153 publications
(109 citation statements)
references
References 48 publications
2
100
1
6
Order By: Relevance
“…In contrast to patients without known dysphagia, the goal for patients with previously diagnosed pharyngeal dysphagia may be to trial a specific consistency with the hope of either adjusting the diet, or reassessing safety in the setting of fluctuating clinical symptoms . Under these circumstances, an abnormal SEES may allow one to avoid a repeat VFSS even if FEES is unsuccessful, as a known abnormality on VFSS will be predictably present in nearly 90% of patients based on our results.…”
Section: Discussionmentioning
confidence: 88%
See 2 more Smart Citations
“…In contrast to patients without known dysphagia, the goal for patients with previously diagnosed pharyngeal dysphagia may be to trial a specific consistency with the hope of either adjusting the diet, or reassessing safety in the setting of fluctuating clinical symptoms . Under these circumstances, an abnormal SEES may allow one to avoid a repeat VFSS even if FEES is unsuccessful, as a known abnormality on VFSS will be predictably present in nearly 90% of patients based on our results.…”
Section: Discussionmentioning
confidence: 88%
“…These findings have several implications worthy of discussion. In a child who is otherwise naive to instrumental swallow studies and without an established diagnosis of swallow dysfunction, one may wonder if a VFSS is necessary to perform following an abnormal FEES, as it may not provide additional insight . However, if a SEES is performed and is abnormal, VFSS may be more assertively avoided, as swallow abnormalities are likely to exist based on the positive predictive value of the static evaluation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, FEES was found with a slight advantage over VFSS to detect aspiration, penetration, and residues. 47 The limitations of the current study are its retrospective nature, small study group, and different swallowing and aspiration assessment tools. Moreover, a majority of the patients were assessed by noninstrumental (bedside) swallowing evaluation with lack of consistency and objective grading.…”
Section: Discussionmentioning
confidence: 93%
“…Clinically, FEES has the advantage of being mobile, having no risk of radiation exposure, and in some clinical settings following specialist training the SP may act as endoscopist reducing the need for additional clinical staff. In addition, a systematic review of 52 articles identified a greater sensitivity in FEES than VFSS in detecting aspiration and penetration, however sensitivity to detecting pharyngeal residue was similar in both tests (Giraldo-Cadavid et al, 2017). However, the procedure is considered more invasive and is not appropriate for patients who are severely confused, have severe movement disorders, or have experienced head and neck trauma which may be impacted by the presence of the nasendoscope.…”
Section: Instrumental Swallow Assessmentmentioning
confidence: 99%